Characterization of Candidate probionts isolated from human breast milk - Khalkhali, S.; Mojgani, N. (Cellular and Molecular Biology, 2017)
This study was designed to isolate and identify the potential probionts present in 32 healthy mothers' breast milk. Microbial culture media and 16SrRNA sequencing were used to isolate and identify the bacteria and all isolates were analyzed for their antagonistic potential, resistance to acidic pH, bile salts and survival under simulated gastric and intestinal conditions. The colonization potential was further assessed based on adherence to human enterocyte-like Caco-2 cell lines. The breast milk samples harbored significant numbers of Gram positive and catalase negative (85%) bacteria. Based on 16SrRNA sequencing, these isolates were identified as Lactobacillus casei, L.gasseri, L.fermentum, L.plantarum, Pediococcus acidilactici, and Enterococcus facieum. Among the isolates, P. acidilactici was the most frequent species (71%) present in these samples. Few Gram and catalase positive isolates, Staphylococcus aureus and S.hominiis were also observed. The isolates were viable and unviable in pH 3 and 1.5, respectively, while all isolates survived in 1.0% bile salt. As putative probionts, P.acidilactici 1C showed a significantly higher percentage of adhesion to Caco-2 cells (p< 0.05)than the other two isolates L.plantarum 7A and E.facieum 2C. Bacterial strains isolated from human breast milk were shown to have probiotic properties including anti-infective protection and may be considered as future therapeutics for infants.